Assessment of Potential Probiotic Properties Lactic Acid Bacteria From Shrimp Paste or Belacan - Haitham Ar; Zaiton H; Norrakiah As; Huda-Faujan N (Institute of Research and Journals, 2024)
Non-Indexed Publication